EDUCATION ON THE USE OF MENDELEY FOR CITATION MANAGEMENT FOR STUDENTS - Nurwijaya, Sugian; Sugiarto, Sigit; Ansiska, Paisal (Ngejha, 2023)
References are used to show that the author has conducted sufficient research and obtained an adequate understanding of the topic being studied. References are also used to support arguments and claims made by the author, thus helping to strengthen the quality of the scientific work. One of the reference management Software that can be used for writing references in a scientific work is Mendeley. Mendeley is a reference management Software that can help authors import, manage, and include references in scientific works efficiently and accurately. Participants in this activity were fourth and sixth semester students of the Mathematics Education study program at Muhammadiyah University of Bone. Based on the community service activity that has been carried out, it can be concluded that education on citation management for students can increase their understanding of using Mendeley by more than 90%.